Factorization of groups involving symmetric and alternating groups - M. R. Darafsheh; G. R. Rezaeezadeh (International Journal of Mathematics and Mathematical Sciences)
We obtain the structure of finite groups of the form G=AB where B is a group isomorphic to the symmetric group on n letters Sn, n≥5 and A is a group isomorphic to the alternating group on 6 letters.